Interactive Learning Boost: Leveraging Lumi Education to Enhance Student Learning Motivation - Syaiful Rahman; Moch Ridwan Kamil (Education and Sociedad Journal, 2025)
This study aims to examine the utilization of H5P-based Lumi Education media in enhancing students’ learning motivation. A qualitative case study approach was employed, involving teachers, students, and the principal selected through purposive sampling. Data were collected via observations, semi-structured interviews, documentation, questionnaires, and Focus Group Discussions (FGDs), and analyzed interactively through data condensation, reduction, display, and conclusion drawing, with source and technique triangulation to ensure trustworthiness. The findings reveal that H5P-based Lumi Education media fosters a more interactive, participatory, and student-centered learning environment, where multimedia elements such as instructional videos, interactive quizzes, and activity-based assessments enhance students’ attention, enthusiasm, and engagement. The media also enables teachers to provide more varied learning experiences compared to conventional methods. Success factors include adequate learning facilities, teachers’ digital competencies, and students’ interest in interactive learning, while challenges involve limited internet connectivity, differences in digital literacy, and longer preparation time. These results suggest that H5P-based interactive learning media has strong potential to improve elementary students’ motivation and contributes to the development of adaptive, interactive, and student-centered digital learning tools suitable for the digital era.